IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2015 PADA KUALITAS TENAGA PENDIDIK DI SMK PGRI 1 JOMBANG - Muhamad Khoirur Roziqin; Muhammad Iftakhur Rozaqi (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
This research aims to examine the implementation of the ISO 9001:2015 quality management system on the quality of teaching staff at SMK PGRI 1 Jombang. The research method used is qualitative with a case study approach. Data was collected through observation, interviews and documentation. Data analysis was carried out using content analysis techniques. The research results show that the implementation of the ISO 9001:2015 quality management system has contributed positively to improving the quality of teaching staff at SMK PGRI 1 Jombang. Factors that support this implementation include the commitment of school leaders, the active participation of teaching staff, and the existence of a continuous monitoring and evaluation process. In conclusion, the implementation of the ISO 9001:2015 quality management system can be a strong foundation for improving the quality of teaching staff at SMK PGRI 1 Jombang. The recommendation from this research is the need for regular coaching and training for teaching staff to strengthen understanding and application of ISO 9001:2015 principles. Â Â